Thinking with the eye: Reading material evidence (KULT_online, 2014)
The Look of the Past explores the ways in which historians can make use of material sources as arguments. The general processes of making, using, and perceiving objects are thoroughly analysed as well as the complex methodological tools of description and comparison. As a specialized handbook (although not explicitly stated as such) it offers a pragmatic approach to the integration of objects in research. In four exemplary essays, Jordanova applies the method she explains theoretically, demonstrating its uses. Additionally, the book provides ample information of further reading for each key theme. As a publication, it promotes scholarly transparency and as such it could become a model of ideal academic conduct.